ANALISIS KAUSALITAS UTANG LUAR NEGERI, PERTUMBUHAN EKONOMI DAN KEMISKINAN INDONESIA - Aldiyus Aldiyus; Mike Triani (Universitas Negeri Padang, 2021)
This study aims to analyze the causality between Indonesia's foreign debt, economic growth and poverty. This type of research is descriptive and associative. This study uses time series data in Indonesia from 1970-2019. This study uses the VAR (VECM) analysis method.with the variabel in this study is foreign debt, economic growht and poverty. The results of this study indicate that: (1) There is a one-way causality of the economic growth variable on the foreign debt variable. (2) there is a one-way causality from the poverty variable to the economic growth variable. (3) There is no causality between the foreign debt variable and the poverty variable.